189k views
4 votes
Simplify 6/6^1/4 rational exponents

User Gkcn
by
6.5k points

1 Answer

3 votes

Answer:

we conclude that:


\frac{6}{6^{(1)/(4)}}=6^{(3)/(4)}

Explanation:

Given

The expression is


  • \frac{6}{6^{(1)/(4)}}

To determine

Simplify the expression

Simplifying the expression


\frac{6}{6^{(1)/(4)}}

Apply the exponent rule:
(x^a)/(x^b)=x^(a-b)


\frac{6}{6^{(1)/(4)}}=6^{1-(1)/(4)}

Subtract the numbers:
1-(1)/(4)=(3)/(4)


=6^{(3)/(4)}

Therefore, we conclude that:


\frac{6}{6^{(1)/(4)}}=6^{(3)/(4)}

User Erik Eidt
by
6.4k points